2019
DOI: 10.20524/aog.2019.0429
|View full text |Cite
|
Sign up to set email alerts
|

Validating and expanding the Baveno VI criteria for esophageal varices in patients with advanced liver disease: a multicenter study

Abstract: Introduction:According to the Baveno VI workshop, patients with compensated advanced liver disease, platelet count (PLT) >150,000/μL and liver stiffness measurement (LSM) <20 kPa can avoid screening endoscopy for high-risk varices (HRVs). The purpose of this study was to validate these criteria in a multicenter Greek cohort and consider other approaches that may further decrease the number of endoscopies.Methods:We prospectively enrolled patients with advanced liver disease (defined as LSM >12 kPa) and evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 17 publications
4
13
0
Order By: Relevance
“…The original Baveno VI criteria, based on simple analytical TE values, were well validated in subsequent studies, [5][6][7][8] but were also criticized as being conservative; endoscopies were spared in modest numbers, and most strikingly 40% of unwanted endoscopies still needed to be carried out. In a multicenter study, Protopapas et al 11 further noted that the absence of the Baveno VI criteria predicted the detection of VNT with 100% sensitivity, 15% specificity, 23% positive predictive value (PPV) and 100% negative predictive value (NPV). While validating the Baveno VI criteria, probably for the first time in an exclusively young population, we observed that although the specificity and NPV of the criteria were high (92.3%), the PPV was low (60%) and, most strikingly, two of the five VNT were missed (sensitivity 60%), which is unacceptable in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original Baveno VI criteria, based on simple analytical TE values, were well validated in subsequent studies, [5][6][7][8] but were also criticized as being conservative; endoscopies were spared in modest numbers, and most strikingly 40% of unwanted endoscopies still needed to be carried out. In a multicenter study, Protopapas et al 11 further noted that the absence of the Baveno VI criteria predicted the detection of VNT with 100% sensitivity, 15% specificity, 23% positive predictive value (PPV) and 100% negative predictive value (NPV). While validating the Baveno VI criteria, probably for the first time in an exclusively young population, we observed that although the specificity and NPV of the criteria were high (92.3%), the PPV was low (60%) and, most strikingly, two of the five VNT were missed (sensitivity 60%), which is unacceptable in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…9 The cut-off values of the expanded criteria were set to a platelet count >110×10 9 cells/L and TE <25 kPa, which were substantiated by two additional cohorts and further studies. 10,11 However, neither the original nor the Expanded Baveno VI criteria nor the Baveno VI satellite symposium clearly states whether the above set of rules applies for pediatric and adolescent populations. 4,9,12 This point is of utmost importance as the invasiveness of EGD as well as logistic constraints in resource-poor settings limit the routine use of the procedure in children.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Protopapas et al used PLT/log 10 LSM to refine Baveno VI criteria [ 71 ], and they found that PLT/log 10 LSM ≤ 122,000 μ L −1 × kPa −1 predicted HRV with 100% sensitivity and negative predictive value (NPV), sparing 22 (20.6%) of the patients from unneeded screening endoscopy without missing HRVs.…”
Section: Refinement Of the Baveno VI Criteriamentioning
confidence: 99%
“…A third score, calculated simply by PC/log 10 LS, was evaluated in a prospective study of 107 patients. It was found that values ≤ 122,000/μL × kPa predicted high-risk varices with 100% sensitivity and 100% NPV, which would prevent 20.6% of patients from receiving unnecessary screening endoscopy ( p = 0.003)[ 21 ].…”
Section: Combination Of Liver Stiffness Spleen Diameter and Platelementioning
confidence: 99%
“…Based on these findings that HREV could be excluded with a very low miss rate[ 22 , 23 ], the 2015 Baveno VI consensus conference recommended that surveillance endoscopy is not necessary for patients with compensated cirrhosis who have normal platelets > 150000/mm 3 and LS < 20 kPa[ 2 ]. Many studies including high-volume single center retrospective studies and meta-analyses have validated the Baveno VI recommendation in patients with different etiologies of cACLD (including hepatitis B, hepatitis C, alcohol, and non-alcoholic steatohepatitis) and variable prevalence of EV, ranging from 23% to 65%[ 21 , 24 - 32 ]. Across all of these studies, the overall missed HREV rate has been 2% or less, in keeping with the proposed < 5% threshold defined by Baveno VI.…”
Section: Liver Stiffness and Platelet Count: The Baveno VI Criteriamentioning
confidence: 99%